Effect of holding time on the corrosion potential of SS304 - Purwanto, Hadi; Manshor, Hanisah (Trans Tech Publications, Switzerland, 2012)
Stainless steels suffer from classical sensitization when encounter at certain temperature which results in precipitation of chromium carbide along grain boundary with simultaneous depletion of chromium from near grain boundaries. This study focused on corrosion potential test at different sensitization condition. The degree of chromium carbide precipitation was measured based on thickness of grain boundary. With increasing holding time, the thickness of the chromium depletion zone also increases due to diffusion of chromium into solid solution. Corrosion potential test showed that the heated sample at 700ºC for 60 minutes resulted in highest corrosion current density and shifted its corrosion potential to more active potential. The potential tend to increase with increasing the degree of chromium carbide precipitation.